The effect of eight weeks of combined training on the serum macrophages phenotype of cardiac patients after coronary bypass surgery - Najmeh Ranjbar (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2019)
Introduction: Cardiovascular disease, including atherosclerosis, has an inflammatory background on a molecular scale. In the immune system, various factors activate macrophages, which ultimately lead to various macrophage activities in inflammatory and non-inflammatory conditions. The aim of the present study was to investigate the effect of eight weeks of combined training on serum macrophage phenotype after cardiac arrhythmias and coronary artery bypass graft surgery. Methods: The present study was a quasi-experimentalstudy performed in the Heart Rehabilitation Center of Afshar Hospital in Yazd. 20 male patients after coronary artery bypass graft surgery were divided into the control and combined exercise groups. Functional capacity, body mass index, muscle strength, and waist-to-hip ratio were estimated before training.The combined program was included aerobic and resistance training for eight weeks, three sessions per week. Aerobic training was performed for 15-20 minutes with maximum intensity of 50-80% of maximum heart rate and resistance training program included three upper limb and two lower limb movements with three sets and 10 repetitions. Blood samples were taken before and after eight weeks and macrophage phenotypes were measured by the ELISA method. Data were analyzed through independent t-test and paired t-test using SPSS Inc., Chicago, IL; version 16 software. Results: The combined exercise resulted in a significant decrease in the M1 macrophage (P<0.05) and a significant increase in the M2 macrophage (P<0.05). Conclusion: The results of this study emphasize the usefulness of this training protocol as a means to reduce inflammation and decreasing the mortality and morbidity rates. Conclusion: The results of this study emphasize the usefulness of this training protocol as a means to reduce inflammation and decreasing the mortality and morbidity rates.